2013
DOI: 10.1002/lary.24199
|View full text |Cite
|
Sign up to set email alerts
|

Effect‐site concentration of remifentanil to prevent cough after laryngomicrosurgery

Abstract: Maintenance of remifentanil at Ce 1.5 and 2 ng/mL suppressed coughing without serious adverse events during emergence from anesthesia with propofol and remifentanil in patients undergoing laryngomicrosurgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 17 publications
1
30
1
1
Order By: Relevance
“…20 Although high-dose remifentanil is highly effective for cough suppression, it may result in undesirable events, such as delayed awakening, increased postoperative nausea and vomiting, and prolonged PACU LOS. 4,5 Remifentanil infusion at 2 ngÁmL -1 via TCI depressed spontaneous respirations 5 and was estimated as an effective concentration (EC 95 ) for preventing cough during emergence from anesthesia. 7 Thus, combination (with dexmedetomidine) therapy might be desirable for preventing cough as an alternate to increasing the concentration of remifentanil.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Although high-dose remifentanil is highly effective for cough suppression, it may result in undesirable events, such as delayed awakening, increased postoperative nausea and vomiting, and prolonged PACU LOS. 4,5 Remifentanil infusion at 2 ngÁmL -1 via TCI depressed spontaneous respirations 5 and was estimated as an effective concentration (EC 95 ) for preventing cough during emergence from anesthesia. 7 Thus, combination (with dexmedetomidine) therapy might be desirable for preventing cough as an alternate to increasing the concentration of remifentanil.…”
Section: Discussionmentioning
confidence: 99%
“…3 Several studies have shown that the optimal effect-site concentration (Ce) of remifentanil for cough suppression during emergence ranges from 1.5-2.9 lgÁmL -1 . [4][5][6][7] Further increasing the dose of remifentanil can be effective in preventing coughing but may cause respiratory depression, delay emergence from anesthesia, and increase the incidence of postoperative nausea and vomiting. 4,5 Dexmedetomidine is a selective a 2 -adrenoreceptor agonist that has dose-dependent sedative, analgesic, and sympatholytic properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Reported cases highlight the role of vigorous coughing in potentially favouring airway rupture related to mechanical tracheal intubation when a double-lumen tube (DLT) is used. 6,7 Many pharmacological and non-pharmacological techniques have been used to reduce coughing at emergence in patients with single-lumen endotracheal tubes (ETTs) in place, [8][9][10][11][12] but these methods have not been applied to the situation of DLTs used chiefly in thoracic surgery. When using a DLT, the overall chosen diameter is normally greater than that of an ETT, and the DLT is in contact with a greater area of the tracheobronchial tree, increasing the potential for cough stimuli.…”
mentioning
confidence: 99%
“…Entrega datos con alta precisión para alcanzar y mantener concentraciones deseadas en sitio efecto, proporcionando una ventaja con respecto a la administración farmacológica de acuerdo con dosis estándar. Dichas concentraciones (según objetivos terapéuticos) han sido reportadas por diversos autores [26][27][28][29][30][31] .…”
Section: Desempeño Del Algoritmo Y Variabilidadunclassified